المنهج التكاملي لتعليم اللغة العربية للناطقين بغيرها: المستوى المتقدم نموذجاً - Ibrahim Youssef, Mohamed Abdelrahman; Bawazir, Mohammed A. (USIM PRESS, 2025)

(untitled)
There are various approaches and perspectives in preparing educational materials for non-native Arabic learners. Some experts present the skills separately, while others incorporate parts of them within the folds of the lessons, among other methods. Consequently, the researchers examine the educational framework for a proposed curriculum based on the integrative approach, designed for non-native Arabic-speaking students in language centers at Malaysian universities, prior to their enrollment in Arabic language and Islamic studies departments. The researchers relied on the descriptive and inductive method, and the study reached several conclusions, including that the curriculum based on the integrative approach achieves an appropriate level of language immersion by combining all branches and skills of the Arabic language. Additionally, the inclusion of idiomatic expressions within narrative texts enhances communication between the Arab and Malay cultures.